(untitled) (Journal of Contemporary Issues in Accounting, 2023)
This study investigated the effect of corporate reporting regulation and sustainable development of Africa with evidence from 54 signatories to the Africa Continental Free Trade Area from 2002-2021. Two specific objectives were the focus of the study and corresponding two hypotheses were formulated for the study. Ex-post facto research design was employed in the study. The population of the study included all 54 signatories to the Africa Continental Free Trade Area from 2002-2021. The study relied on secondary sources of dataset which was obtained from websites of relevant authorities IFRS foundation, Global Reporting Initiative, United Nations Global Compact, Sustainable Stock Exchange Initiative, World Bank, International Monetary Fund, UN Statistics Division and official documents of states. Amongst other preliminary analysis and tests, the panel least square regression analysis was done in validating the hypotheses. The study found IFRS adoption to have significant positive effect on the economic development of signatories to the AfCFTA with p-value = 0.0000. The study also found a significant negative effect on the attainment of sustainable development goals (SDG1-Poverty) of signatories to the AfCFTA with p-value = 0.0216. Consequent on the findings of the study, it is recommended that signatories to the African Continental Free Trade Area agreement should make the IFRS a compulsory financial regulation standard for members as this has shown evidence of improving transparency in reporting thereby enhancing foreign investors’ trust which ultimately increases FDI creating ripple effect on gross domestic products and reduces poverty in the area.